Erni Cabat$1 (Bs magical world of dinosaurs s - Cabat, Erni.; Butler, Lollie, 1938- (Tucson, Ariz. : Great Impressions, 1989)
Presents paintings of several dinosaurs accompanied by humorous poems.
Keywords: Cabat, Erni -- Juvenile literature; Dinosaurs in art -- Juvenile literature; Dinosaurs in art; Dinosaurs -- Poetry